Ultrasound-assisted hydrolysis of lard for free fatty acids catalyzed by combined two lipases in aqueous medium. Issue 1 (1st January 2020) - Huang, Jinjin; Zhao, Qingyi; Bu, Wei; Zhang, Chunmei; Yang, Zhen; Zhang, Xin; Zhang, Kaini
ABSTRACT: Lard is a by-product of animal processing. It is inexpensive compared with vegetable oils; however, its use is limited due to the high calorific value and high-saturated fatty acid content. While using lard as the source of free fatty acids (FFA) can significantly increase its utilization value. This study aimed to research the method on efficient hydrolysis of lard catalyzed by combi -lipases and assisted with ultrasound pretreatment. A 1, 3-specific lipase from Rhizomucor miehei (termed pRML, 1540 U/mL) and a nonspecific mono- and diacylglycerol lipase from Penicillium cyclopium (termed MDL, 2000 U/mL) were used as biocatalysts. Results showed that the maximum hydrolysis rate of lard after 6 h at 45°C by using pRML and MDL alone was, respectively, 39.9% and 8.5%. When pRML combined with MDL ( combi -lipases), hydrolysis rate can reach to 78.1%. While combi -lipases were assisted with 5 min ultrasound pretreatment before the reaction, the hydrolysis rate can further increase to 97%. The combi -lipases with different specificity and assisted with ultrasound pretreatment may be a useful technology for the enzyme production of FFA from complex lipid substrates, such as lard. Graphical Abstract: Abbreviations: FFA: free fatty acids; TAGs: triacylglycerols; SEs: steryl esters; WEs: wax esters; pRML: Rhizomucor miehei lipase; MDL: Penicillium cyclopium lipase; BMGY/BMMY: buffered complex glycerol/methanol medium; BSMG: base salt media with Na2 GP as phosphate source; YNB: yeast nitrogen base W/O amino acids; GC: gas chromatography; TLC: thin-layer chromatography;